DIW Berlin economic outlook: Global economy recovering swiftly; German economy gaining momentum - Geraldine Dany-Knedlik; Guido Baldi; Nina Maria Brehl; Hella Engerer; Angelina Hackmann; Pia Hüttl; Konstantin Kholodilin; Frederik Kurcz; Laura Pagenhardt; Marie Rullière; Jan-Christopher Scherer; Teresa Schildmann; et al. (DIW Weekly Report, 2024)
The German economy began recovering at the beginning of 2024 and has developed better than initially expected. A sharp rise in construction investment, albeit more of a flash in the pan as a result of mild winter weather, along with strong goods exports helped the economy onto its recovery path and masked the disappointing development of private consumption, which sank unexpectedly. However, consumer sentiment has since brightened considerably: Following the recent special payments, employees in many sectors are now earning more on a permanent basis due to pay raises, which increases income security. In conjunction with the inflation rate now being stable at below the three-percent threshold, real wages are rising significantly. Added to this is the turnaround in interest rates initiated by the European Central Bank, which is making saving less attractive and loans more affordable. The UEFA European Men's Football Championship, which is being held in Germany this year, is also likely to boost consumption, albeit slightly. In addition to private consumption, foreign trade will prove to be the second mainstay of the German economy in the forecast period. On the one hand, imports are increasing as the domestic economy becomes stronger. On the other hand, the German export industry will also experience a significant boost, as industrial production is likely to pick up worldwide. Due to the high share of intermediate products and investment goods, exports 'made in Germany' are particularly dependent on the global industry's economic situation. In Germany, too, industrial companies will begin investing more in their capacities from 2025 at the latest. Construction investment will then also rise again. Overall, the outlook is somewhat more positive than it was in the spring: Instead of stagnating, DIW Berlin now expects the German economy to grow by 0.3 percent in 2024 and by 1.3 percent in 2025. One risk factor for the forecast is that the full extent of the damage from the flooding in southern Germany is still unclear. In some places, production capacities could remain impaired for longer than expected. At the same time, it is also conceivable that repair and reconstruction work could increase economic output. Overall, however, the effects in one way or the other are likely to remain manageable. In addition, the tug-of-war over the next federal budget could once again become a factor contributing to uncertainty, possibly even more so than was already to be expected after the results of the EU elections in Germany. The global economy will also gain some momentum over the forecast period. The euro area is finally overcoming its weak phase for good and international trade is picking up speed. The interest rate turnaround in the major advanced economies will likely have a positive effect on residential construction and corporate investments from the second half of 2024. Overall, the global economy is expected to grow by 3.7 percent in 2024 and by 3.6 percent in 2025.
Keywords: E32; E66; F01; 330; Business cycle forecast; economic outlook